nkhuku
contestada

please help!! simplify. Your answer should only contain positive exponents. 2m squared times 2m to the power 3. m to the power 4 times 2m to the power 3

Respuesta :

Answer:

A).4m^(+5)

B).2m^ (+7)

Step-by-step explanation:

First let me convert the expression to words for easy simplification and evaluation.

2m squared times 2m to the power 3.

= 2m² * 2m³

m to the power 4 times 2m to the power 3

= m⁴ * 2m³

So to evaluate.

We just multiply and get our answer.

For 2m² * 2m³

= (2*2)(m²*m³)

= 4(m(²+³))

= 4m^(+5)

For m⁴ * 2m³

= 2(m⁴*m³)

= 2m(⁴+³)

= 2m^ (+7)

ACCESS MORE